2020
DOI: 10.1016/j.japh.2020.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of hormonal contraceptive furnishing in San Francisco community pharmacies

Abstract: Background: In 2013, California passed Senate Bill 493, which allowed pharmacists to furnish hormonal contraceptives without a physician's prescription. Despite this expanded scope of practice, only 11% of the pharmacies reported furnishing hormonal contraception over the following 6 years. Objectives: Our study objectives were to determine the extent of hormonal contraceptive furnishing and identify the factors that led to successful implementation in San Francisco community pharmacies. Methods: Backspace we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 8 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…Contraceptive choice. Twenty-four articles [24,27,39,40,57,58,67,[113][114][115][116][117][118][119][120][121][122][123][124][125][126], sixteen of which were original research studies [24,58,66,67,75,[113][114][115][116]118,120,[122][123][124][125][126][127], gave insight into contraceptive choice. A number of commonly used hormonal contraceptives (e.g., ring, patch, emergency contraception, IUD) were reported to be absent from the military formulary in the US [27], limiting the choice of contraceptive options for servicewomen.…”
Section: Papers Discussed Both North America and The South And Centralmentioning
confidence: 99%
See 1 more Smart Citation
“…Contraceptive choice. Twenty-four articles [24,27,39,40,57,58,67,[113][114][115][116][117][118][119][120][121][122][123][124][125][126], sixteen of which were original research studies [24,58,66,67,75,[113][114][115][116]118,120,[122][123][124][125][126][127], gave insight into contraceptive choice. A number of commonly used hormonal contraceptives (e.g., ring, patch, emergency contraception, IUD) were reported to be absent from the military formulary in the US [27], limiting the choice of contraceptive options for servicewomen.…”
Section: Papers Discussed Both North America and The South And Centralmentioning
confidence: 99%
“…Hormonal contraception. While some evidence suggests that the use of hormonal contraception did not increase during the Zika outbreak, there is mixed evidence on whether hormonal contraception use increased during the COVID-19 pandemic [120,121]. There is evidence to suggest that the use of emergency contraception in clinics increased during the COVID-19 pandemic [39].…”
Section: Papers Discussed Both North America and The South And Centralmentioning
confidence: 99%
“…24 The accessibility of community pharmacists can benefit patients receiving contraceptive prescriptions and enhance contraceptive adherence. 25 Pharmacists already reported their intention to prescribe contraceptive in their practice. 26 The willingness of pharmacists to provide this service is demonstrated across states that have adopted these policies.…”
mentioning
confidence: 99%
“…In San Francisco, 21 of 113 community pharmacies in the city provided pharmacist-prescribed contraceptives. 25 In Oregon, the first state to adopt contraceptive prescribing by pharmacies, a survey delivered prior to the policy being enacted showed that 39% of pharmacists planned to provide contraceptive prescribing. 28 Although only 39% of pharmacists planned to provide contraceptive prescribing, this represents a large increase in access for patients who were previously unable to use pharmacies to obtain this service.…”
mentioning
confidence: 99%
See 1 more Smart Citation